The role of hydro-climatic changes on paleolandscape evolution and on prehistoric settlement during the last humid-arid cycle in the horn of Africa - (:unkn) unknown (My University, 2021)
During the last fourteen thousand years, East Africa was the locus of significant climatic and cultural changes, which highly affected landscape evolution and prehistoric ways of life. Enhanced monsoonal precipitations over the tropics, mainly driven by Earth’s precessional and eccentricity orbital parameters, were the primary causes of the African Humid Period (AHP; ~14 - ~6 ka). This humid period led to the transgression of continental lacustrine waterbodies, the increase of fluvial discharge and the spread of vegetation cover over the present-day desertic regions. The onset and the end of this wetter phase were not homogeneous across the continent, and the AHP was punctuated by centennial-scale episodes of hyper-aridity which varied in time and in space. This highly variable environmental scenario was the theatre of one of the most important socio-economic changes in human history, that of the transition between the last hunters-gatherers and the first food production societies. The concomitance of such cultural transformations and climatic disruptions raises the question of the role of changing environmental conditions on the distribution patterns of new socio-economic practices, namely herding.The Ethiopian Highlands (EH) represent a major receiver of monsoonal precipitations in East Africa. During the AHP, substantial variations of the monsoon regime affected the functioning of the hydro-systems originating in the EH. This included the Blue Nile River and Lake Abhe, the endorheic receptacle of the Awash River waters, and located in the northern East African Rift System (EARS). Additionally, the Nile valley and the EARS, constituted the main corridors for prehistoric human trajectories across the Horn of Africa. With the aim to better understand human-climate coevolution during this crucial period a multiscale and multidisciplinary approach is proposed.First, I decipher Holocene climatic variations from the functioning of the two main EH-origina
Keywords: African Research